Competency Test of Engineering Drawing Design Engineering Using the Online Method - W. Wilarso; Alfiyah Afriliyanti; Jujun Juniadi; M. Mujiarto (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The COVID-19 pandemic made all teaching and learning processes at SMK YAF-Banjar conducted online, to prevent the widespread transmission of Virus-COVID-19. Students continue to learn at home according to the schedule of lessons from school. The competency test of students' machine design drawings conducted by the school is done online so that the competencies of students in grade 12 meet the educational standards and requirements for graduating students to face the workforce. The purpose of the online competency test is to test students' abilities in terms of machine image design. The method used in the student competency test is to contact every student who studies at SMK YAF. The results and discussion in this competency test the results carried out have not been maximized, due to signal constraints where students live, then from the online competency test 3 criteria are communicated including, 1) knowledge, 2) skills, 3) attitude. From the results of the assessment of knowledge and skills the average value is 75. From this value it must still be improved in terms of knowledge and skills. In the knowledge, criteria is an understanding of SOP and applying quality standards of work, while for skills are the results, including 3D arrangement drawings, detailed drawings of 2D components, projections and cuts, grading, linear and geometrical tolerances, markings of work and roughness prices.